Surgical management and outcomes for stage 1 malignant ovarian germ cell tumours: A UK multicentre retrospective cohort study. (April 2022) - Graham, Radha; MacDonald, Nicola D.; Lockley, Michelle; Miller, Rowan; Butler, John; Murali, Krithika; Sarker, Shah-Jalal; Banerjee, Susana; Stoneham, Sara; Shamash, Jonathan; Liberale, Viola; Berney, Daniel M.; et al.
Highlights: This comprehensive analysis identifies low rates of complete surgical staging. In this cohort, the absence of surgical staging did not impact upon recurrence risk. Ovarian cystectomy for immature teratoma did not increase tumour recurrence rates. Abstract: Objective: To describe the current surgical management of stage 1 malignant ovarian germ cell tumours and correlated oncological outcomes. Study Design: We undertook a retrospective study of all stage 1 primary ovarian germ cell tumours treated in four major UK gynaecology oncology centres over 12 years. We assessed route of surgery, fertility-sparing approaches, ovarian cystectomy alone, and surgical staging and correlated these with clinical outcomes. Results: Eighty-six patients were followed-up for a median of 4.4 years (IQR 4.3). The median age was 26 (range 11–47). There were 24 (27.9%) dysgerminomas, 13 (15.1%) yolk sac tumours, 10 (11.3%) mixed germ cell tumours, and 39 (45.3%) immature teratomas. Overall survival was 96.6% (OS, 95% CI 91.9–100%), with event free survival of 81.8% (EFS, 95% CI 72.5–92.3) at 5 years. The majority had fertility-sparing surgery (93%, n = 80). In a subset of patients with immature teratoma, there was no significant difference in recurrence or survival if patients underwent unilateral cystectomy only or salpingo-oophorectomy. Laparotomy was the most common approach (n = 66, 76.7%), used more frequently for larger tumours > 10 cm. Surgical staging procedures were undertaken in 42 (48.6%) patients with no significant difference in rates of staging across histological subtypes. Peritoneal biopsies were taken in 11 (12.7%), omental assessment in 40 (46.5%) and lymphadenectomy in 10 (11.6%). There was no significant difference in EFS between patients who underwent staging procedures (83%, CI 71–98%) versus those that did not (84%, CI 72–98%). There was no significant difference in the rate of staging procedures in paediatric (42.1% 8/19) and adult (57.9% 34/67) populations. Conclusions: Across all histologies and ages, the absence of surgical staging did not impact upon disease free or overall survival in this cohort. This study also raises the possibility of a role for ovarian cystectomy in immature teratoma. These findings warrant investigation in larger prospective studies.